Natural recovery of Zostera noltii seagrass beds and benthic nematode assemblage responses to physical disturbance caused by traditional harvesting activities - Branco, Jordana (2019)
In the intertidal seagrass beds of Zostera noltii of Mira estuary (SW, Portugal) the harvesting practices are frequent. The traditional bivalve harvesting not only affects the target species as the remaining biological assemblages. The main aim of this study was to assess the disturbance caused by sediment digging in the recovery of the seagrass beds habitat, through an experimental fieldwork. The responses of the seagrass plant condition, the sediment microbial activity and the nematode assemblages were investigated after the digging activity in seagrass beds. A total of four experimental plots were randomly demarcated in situ, two plots were subjected to the disturbance - “Digging” - while other two were “Control”; the sampling occurred in five occasions, from May to October: T0–before digging; T1–14 days after digging; T2–45 days; T3–75 days; and T4–175 days. The environmental variables measured in the sediment and the photosynthetic efficiency (α) of the Z. noltii plants in each plot and sampling occasion registered similar values, throughout the experiment. The extracellular enzymatic activity (EEA) clearly presented a temporal pattern, although no significant differences were obtained between digging and control plots. Nematode assemblages registered high densities, revealing the absence of the digging effect: control plots maintained similar density and diversity throughout the experiment, while the density and diversity between digging plots was significantly different at T0 and T4; the trophic composition was similar for both control and digging plots, characterized mainly by non-selective deposit feeders (1B) and epigrowth feeders (2A). Organic matter, nitrate and mean grain size explain a significant amount of the variation in the nematode genera composition. This study demonstrated the capacity of the seagrass habitat to recover under low intensity physical disturbance associated to harvesting.